Listening from within a digital music archive : metadata, sensibilities, and music histories in the Danish Broadcasting Corporation's music archive - Pedersen, Andreas Helles (Lund studies in arts and cultural sciences, 2023)
This thesis examines how digital music archives can facilitate different versions of the history of recorded music. It argues that digital technologies and metadata enable coexisting historical narratives of recorded music that move across time and musical genre, and that can cross geographical and cultural space. The study sees a correlation between archival strategies and the presentation of recorded music. It exemplifies this by examining the development and structuration of the digital music archive of the Danish Broadcasting Corporation (DR). The thesis amplifies that the presentation of recorded music on DRs in-house digital music platform /Diskoteket can impact how the music is perceived. It is asserted that music streaming experiences are directed by imaginaries of the history of recorded music, which can be guided by metadata. As this study is the first to have an explicit focus on DRs music archive, it also offers a historical perspective alongside its more practical and technological analyses. The thesis traces the inner workings of DRs digital music archive and assesses how its architecture makes for multiple and parallel histories of recorded music. It concludes that formations of metadata have the capability to deepen and change the perception and reception of music releases. The thesis argues that metadata give structure to DRs digital music archive while also giving it meaning and purpose, and it suggests that this applies to all types of digital music archives.
Keywords: Danmarks Radio; Ljudarkiv; Metadata; Digitala arkiv; Sound archives